Influence of luting agents on time required for cast post removal by ultrasound: an in vitro study - Janir Alves Soares; Manoel Brito-Júnior; Dimitri Ribas Fonseca; Anielo Faleiro Melo; Suelleng Maria Cunha Santos; Nadia Del Carmen Soto Sotomayor; Neilor Mateus Antunes Braga; André Luis Faria e Silva (University of São Paulo, 2009)
OBJECTIVE: This in vitro study evaluated the influence of luting agents on ultrasonic vibration time for intraradicular cast post removal. MATERIAL AND METHODS: After endodontic treatment, 30 roots of extracted human canines were embedded in resin cylinders. The post-holes were prepared at 10 mm depth and their impressions were taken using autopolymerizing acrylic resin. After casting procedures using a nickel-chromium alloy, the posts were randomly distributed into 3 groups (n=10) according to the luting material: G1- zinc phosphate (SS White) (control group), G2 - glass ionomer cement (Vidrion C; SS White), and G3- resin cement (C&B; Bisco). In G3, the adhesive procedure was performed before post cementation. After 24 h, the cement line was removed at the post/tooth interface using a fine diamond bur, and the ST-09 tip of an Enac ultrasound unit was applied at maximum power on all surfaces surrounding the posts. The application time was recorded with a chronometer until the post was completely dislodged and data were analyzed by ANOVA and Tukey's test (p<0.05). RESULTS: The roots were removed from the acrylic resin and inspected to detect cracks and/or fractures. The means for G1, G2, and G3 were 168.5, 59.5, and 285 s, respectively, with statistically significant differences among them. Two G3 posts resisted removal, one of which developed a vertical fracture line. CONCLUSIONS: Therefore, the cement type had a direct influence on the time required for ultrasonic post removal. Compared to the zinc phosphate and glass ionomer cements, the resin cement required a longer ultrasonic vibration time.